2012
DOI: 10.4314/ajtcam.v9i4.19
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of <em>Opuntia Ficus Indica</em> and <em>Pistacia Lentiscus</em> Seed Oils in Mice

Abstract: Opuntia ficus indica and Pistacia lentiscus L. seeds are used in traditional medicine. The objective of this study was to investigate the toxicity of the fixed oil of Opuntia ficus indica and Pistacia lentiscus L. seeds in mice through determination of LD 50 values, and also the physicochemical characteristics of the fixed oil of these oils. The acute toxicity of their fixed oil were also investigated in mice using the method of Kabba and Berhens. The fixed oil of Pistacia lentiscus and Opuntia ficus indica se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 12 publications
3
12
6
Order By: Relevance
“…The value of the density measured for this oil was 0.9154 g/cm 3 . This value is consistent with the values reported by Boukeloua et al (2012), namely a density in the range of 0.918±0.02. The value is of the same order as those found in some vegetable oils; olive oil (0.910 to 0.916), palm oil (0.895 to 0.900), avocado oil (0.910 to 0.920) (Karleskind, 1992).…”
Section: Physicochemical Parameters Of the Vegetable Oil Of Pistacia supporting
confidence: 93%
See 2 more Smart Citations
“…The value of the density measured for this oil was 0.9154 g/cm 3 . This value is consistent with the values reported by Boukeloua et al (2012), namely a density in the range of 0.918±0.02. The value is of the same order as those found in some vegetable oils; olive oil (0.910 to 0.916), palm oil (0.895 to 0.900), avocado oil (0.910 to 0.920) (Karleskind, 1992).…”
Section: Physicochemical Parameters Of the Vegetable Oil Of Pistacia supporting
confidence: 93%
“…This value for our sample was 8.515 mg KOH g −1 . This value is closed to that reported by Boukeloua et al (2012) concerning this oil, which was 5.891 to 6.203. Charef et al (2008) have reported an acid values of 7.7±0.3 and 24±0.5 mg KOH g −1 , for lentisk oil respectively extracted from black and red berries.…”
Section: Physicochemical Parameters Of the Vegetable Oil Of Pistacia contrasting
confidence: 83%
See 1 more Smart Citation
“…The dose of NaAsO 2 and the period of treatment were selected on the basis of previous studies (Pal & Chatterjee, 2004;Yousef et al, 2008), whereas Pistacia lentiscus oil dose was selected from previous studies on experimental animals (Boukeloua et al, 2012;Djerrou et al, 2010Djerrou et al, , 2011. All experimental procedures were carried out according to the National Institute of Health Guidelines for Animal Care and approved by the Ethics Committee of the University.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Some pharmacological properties of this oil were recently investigated as cicatrizing activity (Djerrou et al, 2010), protection of mercury intoxication (Tounes et al, 2008), investigation of hepatoprotective effect against carbontetrachloride (Maameri et al, 2015). To ascertain the safety of this vegetable oil for its consumers, some studies were conducted as effects on glycemic index, liver and renal functions in rabbits (Djerrou et al, 2011), acute toxicity in mice (Boukeloua et al, 2012), irritancy potential and subacute dermal toxicity in rabbits (Djerrou et al, 2013), subchronic oral toxicity in rabbits (Maameri et al, 2016).…”
Section: Introductionmentioning
confidence: 99%